1979
DOI: 10.21273/jashs.104.6.759
|View full text |Cite
|
Sign up to set email alerts
|

Reflective Film Mulches Influences Insect Control and Yield in Vegetables1

Abstract: In field tests, the most effective film mulch in deterring insects and reducing insect damage to fruits was aluminum. The insects affected were aphids, brown stink bugs, aphid parasites, and Diabrotica spp. Mosaic virus diseases were reduced among aluminum-mulched squash (Cucurbita pepo L.) and cucumber (Cucumis sativus L.) plants. Plant growth, flowering, and fruiting were delayed in tomatoes (Lycopersicon esculentum Mill.) and southernpeas (Vigna unguiculata (L.) Walp.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Our study also documents that the silver plastic mulches were shown to significantly reduce the number of virus-infected tomatoes compared to no mulch. Our results were consistent with the previous studies indicating that the tomato plants grown on silver mulches had a lower incidence of TCSV [ 40 ] and TSWV (related to TCSV) than plants grown on non-UV reflective plastic mulches [ 38 , 39 ]. It can be argued that silver mulches modify the light environment around the plants without causing any phytotoxicity and thus reduce the thrips activity [ 28 , 57 , 73 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study also documents that the silver plastic mulches were shown to significantly reduce the number of virus-infected tomatoes compared to no mulch. Our results were consistent with the previous studies indicating that the tomato plants grown on silver mulches had a lower incidence of TCSV [ 40 ] and TSWV (related to TCSV) than plants grown on non-UV reflective plastic mulches [ 38 , 39 ]. It can be argued that silver mulches modify the light environment around the plants without causing any phytotoxicity and thus reduce the thrips activity [ 28 , 57 , 73 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we revealed a low population of adult thrips and larvae on the silver reflective plastic mulches compared to the other plastic mulches and no mulch, irrespective of tomato leaves and flowers in both 2018 and 2019. Several research studies indicated the advantages of reflective mulches to reducing thrips population in host plants, including row vegetable crops such as tomato and capsicum [ 31 , 32 , 36 , 38 , 68 , 69 , 70 ]. The use of plastic mulch for row crops improved marketable yield, suppressed weeds, and increased the efficient use of water and fertilizers [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation